Keharusan Baralek Sebagai Syarat Akad Pernikahan Dalam Masyarakat Nagari Sungai Nanam Kab. Solok - Silfi Oktarina Suryani; Yasrul Huda; Hamda Sulfinadia (JURNAL ILMIAH RESEARCH AND DEVELOPMENT STUDENT, 2024)
Abstract. Abstract. The research objective in this study is to look at community customs in maintaining the baralek tradition so that the implementation of baralek is used as a condition for marriage contracts in the Sungai Nanam community, Lembah Gumanti District, Solok Regency. Formulation of the problem of how the baralek process is carried out and looking at the necessity of baralek and looking at the impact of Islamic law on the necessity of baralek in the Sungai Nanam community, Lembah Gumanti District, Solok Regency. Type of field research (field research. Data collection techniques through observation, interviews and documentation. The results of this research are: first, the procession for implementing the baralek obligation in the Sungai Nanam community was initially carried out with manyilau, after that the procession of proposing marriage, mahanta siriah, balatak tando, new marriage contract Entering the baralek procession, the factors that require the implementation of baralek are customs, social status, economics and education. According to traditional Islamic law, the requirement to carry out baralek as a condition of the marriage contract in the Nanam River community is included in the category that is more detrimental because after the implementation of baralek there is a debt that must be incurred. paid by the family and the bride and groom can be classified as 'urf-fasid if it is done excessively.